Development trend and application analysis of blockchain with 5G - Dandan XU; Yunyong ZHANG; Daolin ZHANG; Di ZHANG; Xiao WANG; Yixin CAI (Dianxin kexue)
Through the evolution from the information internet era of large connections and large collaborations to the era of strong trust and strong security,the blockchain has triggered a multi-wave technology wave with its characteristics of openness,transparency and decentralization,becoming the new generation of information technology development trends.Starting from the dimensions of technology,people's livelihood and industry,the infrastructure and evolution trends reveal that the blockchain was the essence of the reorganization and re-innovation of the existing technology.The applications were re-divided into the currency circle and chain ring from a technical perspective.By comparing the blockchain technology with 5G technology,the innovative application scenarios of the decoupling and cross-integration were explored that may be involved in the future of the blockchain.